(untitled) (Scientific journal of the Fergana State University, 2023)
This article discussed the linguistic features of some cultures in the Khorezmian dialect and analyzed them in detail. This article contains valuable information about the Uzbek farmers` agricultural lexicon and its development, features of farming lexion, variability in the agricultural vocabulary of the Uzbek language and some other languages of the Uzbek language of Khorezm has found its reflection